Brave talk building resilient relationships in the face of conflict. - MARTIN, MELODY STANFORD (BROADLEAF Books, 2020)
When we disagree about fundamental issues, it can be difficult to maintain close relationships. In Brave Talk, communications expert Melody Stanford Martin teaches us to treat every conflict as if it's an impasse. By learning to temporarily suspend our desire to resolve differences, we make space for deeper understanding and stronger ties. Brave Talk blends humor, creativity, and interactive learning to help everyday people develop better skills for navigating conflict.